ENHANCEMENT OF DISSOLUTION RATE AND FORMULATION DEVELOPMENT OF EFAVIRENZ TABLETS EMPLOYING STARCH PHOSPHATE A NEW MODIFIED STARCH (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
The objective of the study is to prepare, characterize and evaluate starch phosphate, a new modified starch as a carrier in solid dispersions for enhancing the dissolution rate of Efavirenz. The feasibility of formulating solid dispersions of Efavirenz in starch phosphate into compressed tablets with enhanced dissolution rate was also investigated. Starch phosphate was prepared by reacting starch with di-sodium hydrogen orthophosphate anhydrous at elevated temperatures. It was insoluble in water and has good swelling (400%) property without pasting or gelling when heated in water. Solid dispersions of Efavirenz in starch phosphate were prepared by solvent evaporation method employing various weight ratios of drug: starch phosphate such as 2:1(SD-1), 1:1(SD-2), 1:2(SD-3), 1:3(SD-4) and 1:9(SD-5) and were evaluated for dissolution rate and efficiency. All the solid dispersions prepared gave rapid and higher dissolution of Efavirenz when compared to pure drug. Dissolution followed first order kinetics. A 13.98 and 31.37 fold increase in the dissolution rate (K1) of Efavirenz was observed with solid dispersions SD-4 and SD-5 respectively. The DE30 was also increased from 10.66% in the case of Efavirenz pure drug to 51.13% and 71.51% in the case of these solid dispersions. Efavirenz (50 mg) tablets were prepared employing Efavirenz alone and its solid dispersions SD-3 and SD-4 by wet granulation method and were evaluated. Efavirenz tablets formulated employing its solid dispersions in starch phosphate gave rapid and higher dissolution rate and DE30 when compared to plain and commercial tablets. A 16.71 and 31.04 fold increase in the dissolution rate (K1) was observed with tablet formulations containing solid dispersions SD-3 and SD-4 respectively when compared to plain tablets.